Twitter data analytics. - Bruns, Axel (Aslib Journal of Information Management: Volume 66, Issue 3., 2014)
It might still sound strange to dedicate an entire ebook exclusively to a single Internet platform. But it is not the company Twitter, Inc. that is the focus; this ebook is not about a platform and its features and services. It is about its users and the ways in which they interact with one another via the platform, about the situations that motivate people to share their thoughts publicly, using Twitter as a means to reach out to one another. And it is about the digital traces people leave behind when interacting with Twitter, and most of all about the ways in which these traces - as a new ty.